INFORMATION TECHNOLOGIES IN THE SYSTEM OF TRAINING OF PHARMACY SPECIALISTS (Education in the 21st Century, 2023)
The paper deals with the problem of using an interdisciplinary approach to the training of future pharmacists in the system of teaching professional disciplines in modern higher medical educational establishment, in particular during practical classes using information technologies in pharmacy. At the current stage of development of information technologies, a high level of computer skills of graduates of higher medical educational establishments of pharmaceutical profile allows one to get a trained specialist ready to work with specialized software that promotes high efficiency of pharmacists, improving service to pharmacy visitors and increasing sales of medicines and medical devices. All this necessitates substantive and methodological adjustments to the training and retraining of pharmaceutical workers with the approximation of their level of education to international standards. That is why the quality of education in higher educational establishments needs to be improved under the conditions of effective organization and informatization of the educational process, introduction of innovative scientific developments in the practice of teaching information technologies in pharmacy, ensuring teachers’ high professionalism, creating modern teaching and clinical bases.
Keywords: pharmaceutical industry, interdisciplinary approach, educational activities, professional disciplines, information technologies in pharmacy, educational process, integration, distance learning, innovations, creativity, curriculum.